2019
DOI: 10.22214/ijraset.2019.2147
|View full text |Cite
|
Sign up to set email alerts
|

Review Paper on Study of Design and Analysis of Go-Kart Chassis

Abstract: This paper focusing on theoretical understanding of the design and engineering aspects of making Go-kart chassis. We are made the Go-kart with a few restrictions. This paper deals with objectives of assumptions, calculation and analysis of Gokart chassis. The design of Go-kart chassis is chosen in such that the kart is easy to fabricate in every possible manner. The main purpose of this review is to explaining the modeling and then further analysis on it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Finally, they conclude that a foldable chassis with a joint makes any vehicle compatible. Hajare et al [2] used SOLIDWORKS software to design the go-kart chassis and ANSYS & HYPERMESH software to do structural analysis on the go-kart chassis. They suggested that for a chassis, a minimum of 3.125 mm thick tubing either square or round cross-section is required for better performance of the vehicle.…”
mentioning
confidence: 99%
“…Finally, they conclude that a foldable chassis with a joint makes any vehicle compatible. Hajare et al [2] used SOLIDWORKS software to design the go-kart chassis and ANSYS & HYPERMESH software to do structural analysis on the go-kart chassis. They suggested that for a chassis, a minimum of 3.125 mm thick tubing either square or round cross-section is required for better performance of the vehicle.…”
mentioning
confidence: 99%